Marine biological value along the Portuguese continental shelf; insights into current conservation and management tools. (October 2018) - Gomes, Inês; Pérez-Jorge, Sergi; Peteiro, Laura; Andrade, Joana; Bueno-Pardo, Juan; Quintino, Victor; Rodrigues, Ana Maria; Azevedo, Manuela; Vanreusel, Ann; Queiroga, Henrique; Deneudt, Klaas
Graphical abstract: Highlights: A marine biological valuation was completed for the Portuguese continental shelf. Four main hotspots of high biological value were identified. Hotspots mostly fall within current and proposed Natura 2000 sites except in the southern region. Quantitative-based approaches assist in guiding conservation management plans. Abstract: The valuation of nature is an inbuilt component of validating environmental management decisions and an important research field for different disciplines related to conservation, economy and ethics. Here, biodiversity was valued using an ecological approach based on the intrinsic value incorporated in biodiversity per se, regardless of any human association . The Marine Biological Valuation protocol was drawn upon the methodology of terrestrial valuation maps, to support the European MSFD environmental status assessment (descriptor 1 – biodiversity) and national marine spatial planning approaches. To apply the protocol on the Portuguese continental shelf we compiled and analyzed national biological databases for a wide taxonomic range of ecosystem components (seabirds, demersal fish, macrobenthos, marine mammals and sea turtles) and assessed the spatial overlap with existing and proposed conservation areas (Natura 2000 network). The resultant maps described patterns of biological value consistent with the physical and biological oceanographic conditions as well as local hydrodynamics of the Portuguese continental shelf. The results of our approach confirm previously identified valuable areas for protection (particularly in the northern and central regions), but also highlights the value of currently unprotected sites, mainly in the southern region. Biological valuation maps showed to be comprehensive tool to compile and spatially analyze biological datasets. By drawing attention to subzones of biological importance, it constitutes a valuable instrument in making appropriate-scale decisions on the spatial allocation of human activities in the context of the Portuguese marine spatial planning, currently facing the pressure and impacts of increased maritime exploitation.